PERAN SUPERVISI KEPALA SEKOLAH MEMODERASI PENGARUH KOMITMEN SEKOLAH DAN KOMPETENSIGURU TERHADAP KINERJA GURU (Studi pada Guru - Guru SD di UPT Disdikpora Kecamatan BawangKabupaten Batang) - Martini, 11 52.02 0064 (Students Journal of Economic and Management, 2013)
This study aimsto analyzethe supervision ofthe school principals commitment andcompetencemoderate theinfluenceof teacherson teacher performancein theprimary schoolteacherwho is acivil servant(PNS), certifiedS1, agedbetween25 to55years, anda minimumlevel IIIinUPTOnionsBatangDistrictEducation Office. The population inthis study wereelementary school teachersnumbered108people. Measurement ofresponses to questionnairesusing a Likert scaleof 7 (seven) alternative answers. Testsusing theinstrumentvalidity andreliability, whiletestingthe modelusingthe coefficientof determinationandF test(Goodness of Fit). Testingthis hypothesisusingquasimoderatorregressionwith a significance level(Î±) of 5%. Hypothesis test resultsobtainedthat theschools commitment and significantpositive effecton teacher performance, teacher competenceinsignificanteffecton the performance ofteachers, principalssupervisingpositive and significant effecton the performance ofteachers, principalssupervisethe schools commitment to strengthenthe influence ofthe performance of teachers, principalsandsupervisionnotmoderate theeffect ofteacher competence onteacher performance. Â  Key words: commitment, competence, headmaster supervision, teacher performance.